Microstructure and crystallographic texture data in modern giant clam shells (Tridacna squamosa and Hippopus hippopus) - Kimberley Mills; Duncan D. Muir; Anthony Oldroyd; Eleanor H. John; Nadia Santodomingo; Kenneth G. Johnson; Muhammad Ali Syed Hussein; Sindia Sosdian (Elsevier Inc., 2024)
This article provides novel data on the microstructure and crystallographic texture of modern giant clam shells (Tridacna squamosa and Hippopus hippopus) from the Coral Triangle region of northeast Borneo. Giant clams have two aragonitic shell layers—the inner and outer shell layer. This dataset focuses on the inner shell layer as this is well preserved and not affected by diagenetic alteration. To prepare samples for analysis, shells were cut longitudinally at the axis of maximum growth and mounted onto thin sections. Data collection involved scanning electron microscopy (SEM) to determine microstructure and SEM based electron backscatter diffraction (EBSD) for quantitative measurement of crystallographic orientation and texture. Post-acquisition reanalysis of saved EBSD patterns to optimize data quality included changing the number of reflectors and band detection mode. We provide EBSD data as band contrast images and colour-coded orientation maps (inverse pole figure maps). Crystallographic co-orientation strength obtained with multiple of uniform density (MUD) values are derived from density distributed pole figures of indexed EBSD points. Raw EBSD data files are also given to ensure repeatability of the steps provided in this article and to allow extraction of further crystallographic properties for future researchers. Overall, this dataset provides 1. a better understanding of shell growth and biomineralization in giant clams and 2. important steps for optimizing data collection with EBSD analyses in biogenic carbonates.